Compensation, Intrinsic Motivation, and Performance: The Mediating Role of Work Discipline among Vocational High School Administrative Staff - Sari, Hani Chotfia; Herdiyana; Yayan Hadiyat (International Journal Administration, Business & Organization, 2026)
This research investigates how compensation and intrinsic work motivation influence the performance of educational support staff in private vocational high schools, while also testing whether work discipline serves as a mediating mechanism. The study stems from the critical role of human resource management in sustaining the effectiveness of educational services, particularly through the contributions of non-teaching staff. Using a quantitative survey design with total sampling, questionnaires were distributed to all 160 staff members, and 115 usable responses were obtained. Data were processed using descriptive statistics and Structural Equation Modeling (SEM). The findings show that compensation does not significantly predict work discipline, whereas intrinsic motivation positively and significantly predicts work discipline. In addition, compensation and intrinsic motivation each have a positive and significant effect on staff performance. Conversely, work discipline does not significantly affect performance. Mediation analysis further confirms that work discipline does not transmit the effects of compensation or intrinsic motivation to performance. Overall, the results imply that performance enhancement efforts should prioritize an equitable compensation system and the strengthening of intrinsic motivation, as work discipline is not supported as the mediating pathway in this context.